2004
DOI: 10.1115/1.1691448
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Orthogonal Fluoroscopic Images to Measure In Vivo Joint Kinematics

Abstract: Accurately determining in vivo knee kinematics is still a challenge in biomedical engineering. This paper presents an imaging technique using two orthogonal images to measure 6 degree-of-freedom (DOF) knee kinematics during weight-bearing flexion. Using this technique, orthogonal images of the knee were captured using a 3-D fluoroscope at different flexion angles during weight-bearing flexion. The two orthogonal images uniquely characterized the knee position at the specific flexion angle. A virtual fluoroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
202
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(205 citation statements)
references
References 17 publications
2
202
0
1
Order By: Relevance
“…Because fluoroscopic resolution is typically between 0.3 and 0.5 mm, it would be difficult to detect out-of-plane translations on the order of 5 mm using only a single image. 7 However, motion of the projected points that would not be discernable in the in-plane projection would be easily detected using an orthogonal image as demonstrated by the dual orthogonal imaging system (Fig. 3B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because fluoroscopic resolution is typically between 0.3 and 0.5 mm, it would be difficult to detect out-of-plane translations on the order of 5 mm using only a single image. 7 However, motion of the projected points that would not be discernable in the in-plane projection would be easily detected using an orthogonal image as demonstrated by the dual orthogonal imaging system (Fig. 3B).…”
Section: Discussionmentioning
confidence: 99%
“…7 Using sphere and cylinder models, the study showed that translation and rotation errors were within 0.1 mm and 0.18, respectively, for all DOF. The study of Li and colleagues suggests that a biplane fluoroscopic technique has an advantage over a single-plane technique due to the ability to detect out-of-plane translation and rotation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,24 At flexion angles <608, as previous investigators pointed out, the internal rotation of the tibia relative to the femur caused by the quadriceps loads could be responsible for the decreasing coronal plane angle. 22,30 At higher flexion angles, the patellar tendon forms a smaller angle with the long axis of the tibia, where a smaller change in rotation with knee flexion was observed. 22,30 The patellar tendon demonstrated an increasing external rotation of its patellar insertion site with respect to the tibial attachment site as the knee flexed.…”
mentioning
confidence: 99%
“…The decreasing sagittal plane angle of the patellar tendon with flexion might correspond to the posterior translation of the femur relative to the tibia during weight-bearing flexion. 22,30 However, the increasing internal tibial rotation (external femoral rotation) with flexion 22,30 corresponds to the less posterior orientation of the medial portion compared to the other portions. The data on the coronal plane orientation were also consistent with observations in the literature.…”
mentioning
confidence: 99%